Comparison of the teeth whitening effect of vitamin C extract of aqueous unripe guava fruit (Psidium guajava) and commercially available bleaching solution - Banzon, Beatriz; Gonzales, Jannyl Alyanna A.; Padilla, Christine Jennifer D.; Pasciolco, Marianne M.; Tablante, Mary Ann S.; Alfaro, Arlene Cecilia A. (Manila Department of Community Dentistry, University of the Philippines Manila, 2018)
Introduction: In the recent years, there has been a growing sector of personal hygiene products such as oral health products, both in the Filipino and international market. Filipino consumers now prefer new products that are affordable and are made of natural ingredients. Filipinos are also shown to be choosing more premium products with additional benefits. In 2006, a study in University of the Philippines College of Dentistry (UPCD) by Pitero and Tadique showed that Vitamin C component from guava is effective in teeth whitening when tested on bovine teeth. In line with that, different bleaching and teeth whitening products are in demand in the market worldwide. This study aims to determine if vitamin C extract from guava fruit is as effective as commercially available bleaching solution as a whitening agent. Shade changes that occurred on extracted human teeth when immersed in artificial saliva and commercially available bleaching solution were also analyzed. Comparison of the shade changes on human teeth immersed in vitamin C extract from guava fruit, commercially available bleaching solution, and artificial saliva was also performed.
Methods: An in vitro experiment which lasted for 5 months was conducted. Forty-five (45) extracted premolars were equally and randomly assigned to three groups. The first group was immersed in the guava extract for 30 minutes (Group G). The second group was fully covered with bleaching solution for 30 minutes (Group B). Lastly, the third group was immersed in artificial saliva (Group C) throughout the experiment. All groups were stored in an incubator with a temperature of 37oC to simulate oral conditions. Shade of each specimen in all three groups was recorded at baseline, day 3, 6, 9, and 23.
Results: For Group G, the teeth significantly lightened for an average of 6 shades from day 0 to day 9 and then darkened for an average of 2 shades until day 23. For Group B, the teeth consistently lightened for an average of 2 shades from day 0 to day 9, but the change was not significant within the group since the teeth darkened for an average of 1 shade by day 23. For Group C, no significant shade changes were noted from day 0 to day 9 and day 23. At day 9, the shade of the teeth in Group G was significantly lighter than the shade of teeth in Group B at 0.10 significance level. Also, the teeth in Group G was significantly lighter than the shade of teeth in Group C at 0.05 significance level. At day 23, results show that there are no significant differences among groups.
Conclusion: From the results, it can be concluded that the whitening effect of the guava extract group is not significant as compared to bleaching solution. However, the teeth immersed in guava extract displayed significant whitening effect within the group.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila
Yes
Keywords: Teeth--Bleaching.; Whitening